Transnational and Transatlantic Fascism, 1918–2018 : The Far Right in East Central and Southeastern Europe (Routledge Studies in Fascism and the Far Right, 2025)
This volume charts the history of transnational and transatlantic fascism in East Central and Southeastern Europe, a lesser-known phenomenon that occurred throughout the twentieth century into the present. Organizations and individuals in this part of the continent, under the influences of Fascist Italy and Nazi Germany, conceptualized their own forms of fascism in the 1920s, 1930s, and 1940s. Due to the heterogenous nature of East Central Europe, fascism took various forms in the territories that prior to 1918 had belonged to the Habsburg, German, Russian, and Ottoman Empires. As a result, East Central Europe became a mosaic of fascist parties, organizations, and movements. During World War II, East Central and Southeastern European fascisms substantially contributed to collaboration with the Nazis and the genocide of the Jews. During the Cold War, East Central and Southeastern European fascists underwent multifaced aesthetic and ideological transformations in the Soviet Union and its satellites as well as in exile in the West. After the collapse of the Soviet Union, the legacy of fascism re-emerged in the region, informing parts of the ideologies of various neo-fascist, radical nationalist, antisemitic, and national conservative parties and movements, as well as motivating communal politicians to erect monuments to fascists, war criminals, and antisemites. With comprehensive coverage through a range of essays, this book is a helpful resource to scholars in European history, political history, and the study of fascism.
Keywords: Fascism; Central Europe; Eastern Europe; Croatia; Romania; Ukraine; Russia; Slovakia; Hungary; Canada; Holocaust; Genocide